Adolescent victims of violence in a welfare state. Sociodemography, ethnicity and risk behaviours - Pedersen, Willy (The British journal of criminology, 2001)
In a normal population sample of Norwegian adolescents, 6 per cent reported to have been victims of violent victimization during the last year. The sample consisted of three cohorts of adolescents from Oslo, aged 13-18, who had filled out a survey at school. Further, we had at our disposal community-level indicators of welfare in the home city districts of the adolescents. Boys were more often victimized than girls. Individual level demographic indicators (immigrant, working-class background, parents unemployed or on social welfare), were associated with victimization risk. However, the impact of community-level sociodemographic variables (education, income, single parenthood, death rates) were of greater magnitude. Further, there were effects from general lifestyle (unorganized leisure, evenings in town), but risk behaviours were more important. In particular alcohol problems, own aggression and carrying a weapon were associated with high risk for victimization. There were small differences in predictors between genders, but adolescents with immigrant background were less vulnerable for contextual level factors than adolescents without such a background. The findings are discussed in relation to other recent findings and theoretical developments as regards research on violent victimization